Fiscal Policies, Green Trade, and Green Bond Market Development: An Empirical Study using Cross-Country Data - Yougang, Blanche Brinda; Zor, Coolin-Campbell M.; Bom, Charles; Alade, Elvis (International Journal of Economics and Financial Issues, 2025)
The global transition toward sustainable finance has elevated green bonds as a pivotal instrument for mobilizing capital toward climate-aligned investments. Yet, empirical understanding of the policy drivers behind green bond issuance remains incomplete, particularly regarding the combined roles of fiscal policy and trade integration. In this study, we examine how environmental taxes, fossil fuel subsidies, public environmental expenditure, and international trade of low-carbon technologies and environmental goods simultaneously affect the development of green bond markets. We use a panel of 11 countries between 2014 and 2022 and estimate fixed effects regression models, concluding that, though environmental taxes are positively related to the issuance of green bonds, they significantly diminish when fossil fuel subsidies persist. Conversely, direct public environmental expenditure and participation in foreign environmental trade, are consistently and robustly significant drivers of green bond issuance. These results highlight the need for coherent policy frameworks, that is, public interventions aiming at scaling up green finance through a recalibration of fiscal signals, an elimination of perverse subsidies and a boost of cross-border trade in green technologies.